Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445393
|View full text |Cite
|
Sign up to set email alerts
|

Provocations from #vanlife

Abstract: Research on how lived experiences with technology intersect with home and work are core themes within HCI. Prior work has primarily focused on conventional life and work in Western countries. However, the unconventional is becoming conventional-several rising subcultures are coming into prominence due to socio-economic pressures, aided by social media. One example-#vanlife-is now practised by an estimated three million people in North America. #vanlife combines travel, home, and work by their occupants (vanlif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Although the official numbers show a global trend of growth in this form of travel, several authors warned about the lack of scientific research on the subject, which has generated some gaps in knowledge about the phenomenon of motorhome travel (Caldicott et al, 2022; Dias and Domingues, 2018; Eager et al, 2022; Espiner et al, 2023; Fieger et al, 2020; Hardy and Gretzel, 2008; Hardy and Kirkpatrick, 2017; Higgs and Quirk, 2007; Kearns et al, 2016; Lashley, 2015; Mahadevan, 2013; Rizvi et al, 2021). This article forms part of a broader investigation aiming to fill some of these gaps.…”
Section: On the Road mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the official numbers show a global trend of growth in this form of travel, several authors warned about the lack of scientific research on the subject, which has generated some gaps in knowledge about the phenomenon of motorhome travel (Caldicott et al, 2022; Dias and Domingues, 2018; Eager et al, 2022; Espiner et al, 2023; Fieger et al, 2020; Hardy and Gretzel, 2008; Hardy and Kirkpatrick, 2017; Higgs and Quirk, 2007; Kearns et al, 2016; Lashley, 2015; Mahadevan, 2013; Rizvi et al, 2021). This article forms part of a broader investigation aiming to fill some of these gaps.…”
Section: On the Road mentioning
confidence: 99%
“…Until recently, most studies suggested that those adhering to this practice were retirees or people in a pre-retirement situation, namely those belonging to the baby boom generation (born between 1946 and 1964) coming from affluent countries (Counts and Counts, 1992, 1996; Holloway, 2007, 2009; Mahadevan, 2014; McHugh and Mings, 1991; Mings, 1997; Onyx and Leonard, 2007; Patterson et al, 2015; Pearce and Wu, 2018; Viallon, 2012; Wu and Pearce, 2017). More recent works, however, point to a growing diversification of the labour situation of motorhome users, as well as their practices and motivations (Eager et al, 2022; Gretzel and Hardy, 2019; Mundet et al, 2023; Rizvi et al, 2021; Zhao, 2020).…”
Section: Travelling In a ‘House On Wheels’mentioning
confidence: 99%
See 1 more Smart Citation
“…Advancements in technology have enabled hypermobile, gig worker lifestyles. A recent study by Rizvi et al (2021) which investigated technology practices within the vanlife community, found technology to be widely implemented across multiple dimensions of vehicle-based living, including finding and keeping community, navigation, recreation, and income generation. These finding echo Darley et al's (2017) investigation of Grey Nomads' engagement with internet and social networking sites, which was conducted with a cohort of Grey Nomads travelling in caravans.…”
Section: Changing Technological Landscapementioning
confidence: 99%